Women in the History of Science A sourcebook - Wills, Hannah; Harrison, Sadie; Jones, Erika; Lawrence-Mackey, Farrah; Martin, Rebecca (UCL Press, 2023)
Women in the History of Science brings together primary sources that highlight women's involvement in scientific knowledge production around the world. Drawing on texts, images and objects, each primary source is accompanied by an explanatory text, questions to prompt discussion, and a bibliography to aid further research. Arranged by time period, covering 1200 BCE to the twenty-first century, and across 12 inclusive and far-reaching themes, this book is an invaluable companion to students and lecturers alike in exploring women's history in the fields of science, technology, mathematics, medicine and culture. While women are too often excluded from traditional narratives of the history of science, this book centres the voices and experiences of women across a range of domains of knowledge. By questioning our understanding of what science is, where it happens, and who produces scientific knowledge, this book is an aid to liberating the curriculum within schools and universities.